Analysis of the Application of Green Accounting in Waste Management in RSUD Lombok Barat - Nihayah, Hairun; Fitriyah, Nur (East Asian Journal of Multidisciplinary Research, 2024)
This research aims to determine the waste management process and green accounting process applied in hospitals. This research was conducted at the Patut Patuh Patju (Tripat) Regional General Hospital, West Lombok. The method used is a qualitative approach. Data analysis was carried out based on information about environmental costs and identifying environmental costs at Tripat District Hospital. The research results show that Tripat Hospital carries out waste management with good environmental quality tests because there are no external failure costs incurred. Apart from that, Tripat Regional Hospital has not implemented green accounting because there is no specific environmental cost report. Researchers use Hansen and Mowen's environmental cost theory to identify and propose environmental cost reports.